The chivalric ethos and the development of military professionalism - Trim, D. J. B. (David J. B.) (History of warfare ;, 2003)
An exploration of the armies and societies of late-mediaeval and early-modern Europe. The essays examine the extent to which the chivalric ethos and military professionalism were incompatible, as well as their relative significance for developments in the art of war, and the rise of the state.